Estimation of agricultural soil erosion and surface water quality trends in the Cheney Lake watershed - Bontrager, Austin (Kansas State University, 2011)
Phosphorus and sediment runoff are the primary cause of eutrophication in Cheney Lake, the primary water source for Wichita, Kansas. Best Management Practices (BMPs) such as no-till farming practices and nutrient management can be implemented to reduce phosphorus runoff on high-risk agricultural fields. Past efforts have established BMP use in this watershed, although the effectiveness of these efforts has not been evaluated. The goals of this project were to identify any existing water quality trends in the Cheney Lake watershed, estimate the current distribution of erosion in the watershed, and evaluate the placement of BMPs with regards to field-scale erosion risk. Parametric, multi-linear regression and non-parametric, seasonal Mann-Kendall analyses were used to identify trends in the Total Suspended Solids (TSS) and Total Phosphorus (TP) of grab samples from the North Fork Ninnescah River. A Geographic Information System (GIS) model based on the Revised Universal Soil Loss Equation (RUSLE) was used to estimate watershed-scale erosion, prioritize agricultural land for BMP placement, and evaluate existing placement of BMPs within the Cheney Lake watershed. No detectible trends were identified in the water quality data due to stream variability, frequency of sampling, or absence of actual improvement in water quality. Additional sampling must be done to detect any trends in the future. BMPs were implemented on 13% of prioritized field area, and 11% of non-prioritized field area. Conservation Reserve Program (CRP) fields were placed on 14% of prioritized field area, and 5% of non-prioritized field area. No-till practices were implemented on 13% of prioritized field area, and 18% of non-prioritized field area. The top 20% eroding fields were identified given current conditions, and account for approximately 56% of the watershed-wide erosion. The GIS method has demonstrated utility in evaluating past erosion control measures for the watershed and in informing future decisions concerning BMP placement.
Keywords: Water quality; Geographic information system; Cheney Lake; Soil erosion; Agronomy (0285)